Is Nodding Syndrome an Onchocerca Volvulus-Induced Neuroinflammatory Disorder? Uganda’s Story of Research in Understanding the Disease - Idro, Richard; Opar, Bernard; Wamala, Joseph; Abbo, Catherine; Onzivua, Sylvester; Mwaka, Deogratius Amos; Kakooza-Mwesige, Angelina; Mbonye, Anthony; Aceng, Jane R. (International Journal of Infectious Diseases, 2016)
The Sustainable Development Goals (SDGs) mandate systematic monitoring of the health and wellbeing of all children to achieve optimal early childhood development. However, global epidemiological data on children with developmental disabilities are scarce. The Global Burden of Diseases, Injuries, and Risk Factors Study 2016 provides a comprehensive assessment of prevalence and years lived with disability (YLDs) for development disabilities among children younger than 5 years in 195 countries and territories from 1990 to 2016.